Populations of the Invasive Mussel Mytella strigata in China Showed Lower Genetic Diversity in Autumn than in Spring - Peizhen Ma; Chenxia Zuo; Shaojing Yan; Xiangyu Wu; Xiaojie Ma; Yi Zhu; Zhen Zhang (Biology)
Native to tropical America, the charru mussel, Mytella strigata, has been spreading rapidly in the West Pacific Ocean, including the South China Sea. In order to study the adaptive evolution of M. strigata and examine the present status of invasion in China, the mitochondrial nad2 gene fragment was employed to analyze the genetic variations of seven populations sampled in both spring and autumn 2023. Results showed that all the populations had high haplotype diversity (>0.5) and low nucleotide diversity (<0.005), suggesting the ongoing rapid expansion following a genetic bottleneck. The Zhanjiang population had the highest genetic diversity in spring with 22 haplotypes, 37 polymorphic sites, and haplotype diversity, nucleotide diversity, and the average number of nucleotide differences being 0.911, 0.00623, and 4.341, respectively. However, in autumn, the Shanwei population had the most haplotypes (11) and polymorphic sites (19), with the highest haplotype diversity value of 0.891, while the Qunjian population had the highest nucleotide diversity (0.00392) and average number of nucleotide differences (2.809). Combining geographic populations by seasons confirmed lower genetic diversity in autumn compared to spring, evidenced by fewer haplotypes and polymorphic sites, reduced haplotype diversity and nucleotide diversity, and lower genetic distance within populations. These findings provided evidence for understanding the molecular characteristics of M. strigata population expansion in China.